Impact of Green Manuring and Nitrogen Fertilization on Rice Cultivation: A Peruvian Amazon Forest Study in San Martín Province - Arevalo Aranda, Yuri Gandhi (2024)
Green manuring is an environmentally friendly technology aimed at providing nutrients to plants, enhancing soil fertility, mitigating soil degradation, controlling weeds and pests, and decreasing reliance on inorganic fertilizers. However, it requires dissemination and support to be adopted, especially in the poorest agricultural communities in Latin America. The study was conducted at the El Porvenir INIA in San Martín, Perú; it assessed two treatment sets: (1) green manure Crotalaria juncea (CroJ), Canavalia ensiforme (CanE), no green manure; and (2) nitrogen fertilizer dose (FN75, FN100). It was arranged in a split-plot design with four replications. During the experiment we detected an important fluctuation in soil parameters, however, it is the diminished levels of soil carbon and nitrogen, which were presumably the outcomes of microorganism processes. Otherwise, we observed that CanE significantly reduced the diseased tillers by "White Leaf Virus" (RHBV) by 2.82% compared to the control. The superior outcomes were achieved through CanE, and the highest yield was 8.36 t.ha¯¹ with the CanE - FN100 treatment. Additionally, the nutritional quality of rice was not altered by green manures or chemical nitrogen fertilization doses tested.